PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN ALIRAN KAS DARI AKTIVITAS OPERASI TERHADAP PRAKTIK EARNINGS MANAGEMENT - Kenny Ardillah (Universitas Bunda Mulia, 2018)
This research examines good corporate governance characteristic such as board of commissioner size, composition of independent commissioner board, committee audit size, composition of independent committee audit, number of committee audit meeting, committee audit financial expertise, and audit quality and also company characteristics such as company size and cash flows from operating activities that affect earnings management practices. his research samples is focused on manufacturer companies listed in Indonesia Stock Exchange for period 2011 – 2014 with total 154 data used in this research. The result of this research is composition of independent commissioner board and company size had positively influence towards earnings management practices. Cash flows from operating activities had negatively influences towards earnings management practices. Commissioner board size, committee audit size, composition of independent committee audit, number of committe audit meeting, committee audit financial expertise, and audit quality had no influence towards earnings management practices. Keywords : Corporate Governance, Earnings Management, Company Size, Cash Flow From Operating Activities